Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.3390/molecules27248919
|View full text |Cite
|
Sign up to set email alerts
|

Strategies Tackling Viral Replication and Inflammatory Pathways as Early Pharmacological Treatment for SARS-CoV-2 Infection: Any Potential Role for Ketoprofen Lysine Salt?

Abstract: COVID-19 is an infective disease resulting in widespread respiratory and non-respiratory symptoms prompted by SARS-CoV-2 infection. Interaction between SARS-CoV-2 and host cell receptors prompts activation of pro-inflammatory pathways which are involved in epithelial and endothelial damage mechanisms even after viral clearance. Since inflammation has been recognized as a critical step in COVID-19, anti-inflammatory therapies, including both steroids and non-steroids as well as cytokine inhibitors, have been pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
(111 reference statements)
0
1
0
Order By: Relevance
“…In this regard, the viral propagation has been reported to be promoted by oxidative stress and several viruses ( e.g., SARS-CoV-2 [ 123 ]), once entered into the host cells, can trigger reactive oxygen species (ROS) and, subsequently, COX-2 activation [ 124 ]. Indeed, COX-2 levels have been reported as increased in response to RSV [ 125 ], FLU-A [ 126 ] and SARS-CoV-2 [ 127 ]. Here, RNAseq data analyses obtained from Caco-2-infected cells show diminished levels of COX-2 and COX-3 in those Solution-3-pre-treated cells (COX2: Fold Changes − 2.8; p-value, 6.35E-11; COX3: Fold Changes − 4.06; p-value, 3.34E-16; Additional file 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this regard, the viral propagation has been reported to be promoted by oxidative stress and several viruses ( e.g., SARS-CoV-2 [ 123 ]), once entered into the host cells, can trigger reactive oxygen species (ROS) and, subsequently, COX-2 activation [ 124 ]. Indeed, COX-2 levels have been reported as increased in response to RSV [ 125 ], FLU-A [ 126 ] and SARS-CoV-2 [ 127 ]. Here, RNAseq data analyses obtained from Caco-2-infected cells show diminished levels of COX-2 and COX-3 in those Solution-3-pre-treated cells (COX2: Fold Changes − 2.8; p-value, 6.35E-11; COX3: Fold Changes − 4.06; p-value, 3.34E-16; Additional file 8 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, even after the virus has been eradicated, the previous SARS-CoV-2 interaction with host cell receptors and consequent activation of pro-inflammatory pathways may still be responsible for endothelial and epithelial damage mechanisms. In this context, anti-inflammatory treatments, such as steroidal and non-steroidal drugs, as well as cytokine inhibitors, have been suggested in the treatment of COVID-19 patients, since inflammation treatment has been identified as a crucial step in the recovery process [7]. The complications observed in COVID-19 patients are numerous, especially in cases of the more severe forms of the diseases.…”
Section: Molecules Against β-Coronavirusesmentioning
confidence: 99%
“…By screening 171 candidates obtained from the DrugBank database (http://www.drugbank.ca/ accessed on 17 February 2023), other in silico studies identified possible organic triazole compounds such as bemcentinib, and bisoctrizole, as M pro inhibitors whose pharmacokinetic characteristics were also evaluated, and their complex stability and conformation were examined using molecular dynamics simulation [11]. Non-steroidal anti-inflammatory drugs, which are frequently used to treat upper airway infections symptomatically, are of crucial importance when administered in the early stages of SARS-CoV-2 infection and, in this context, ketoprofen lysine salt is a non-steroidal anti-inflammatory drug which was suggested to offer notable benefits in early COVID-19 therapy, based on the pharmacodynamic and pharmacokinetic characteristics of this drug [7].…”
Section: Drug Repositioningmentioning
confidence: 99%
“…It needs a parasite to enter a host cell, and then uses the functions of that cell to multiply itself with the following steps. (i) Absorption: Viruses must first bind to receptors on animal cell surfaces [ 35 , 36 , 37 ]. In SARS-CoV-2, this life cycle begins when the surface-protruding S protein binds to the receptor of ACE2, an enzyme protein on the cell surface.…”
Section: Structural Characterization Of Sars-cov-2mentioning
confidence: 99%